2016
DOI: 10.1021/acs.analchem.6b03669
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Cycloolefin Polymer Capillaries for Open Tubular Ion Chromatography

Abstract: We describe novel cycloolefin polymer (COP)-based open tubular capillary ion exchange columns. COP capillaries (inner diameter of 19-28 μm) were successfully sulfonated at room temperature using a cocktail of ClSOH (85-95% w/w) and HOAc or HSO. The cation exchange capacity is controlled by the sulfonation time and the sulfonation solution composition and can be as high as 300 pequiv/mm. Following sulfonation, the capillaries were coated with 65-nm-diameter anion exchanger (AEX) latex nanoparticles that attach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…For chromatographic experiments, capillaries were coated with AS18 latex (COP capillaries were sulfonated before coating); details of COP column preparation appear elsewhere. 21 The OT column injection system used for the capillary columns has been previously described. 13 Figure 1 inset indicates how this injection system is built around the capillary holding tee.…”
Section: ■ Movable Admittance Detectionmentioning
confidence: 99%
“…For chromatographic experiments, capillaries were coated with AS18 latex (COP capillaries were sulfonated before coating); details of COP column preparation appear elsewhere. 21 The OT column injection system used for the capillary columns has been previously described. 13 Figure 1 inset indicates how this injection system is built around the capillary holding tee.…”
Section: ■ Movable Admittance Detectionmentioning
confidence: 99%
“…A 19-μm-diameter COP capillary was sulfonated by chlorosulfonic acid (Acros, www.acros.com) to a capacity of ∼3 peq/mm 2 , and then coated with anion-exchange AS18 latex nanoparticles (65 nm in diameter, courtesy of Thermo Fisher Scientific) that attach to the sulfonated capillary walls electrostatically, to be used as the separation column. 16 The anion exchange capacity was 25 peq/mm 2 . [Note: throughout the paper, peq denotes picoequivalent.]…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…A hydroxide eluent compatible cyclic olefin polymer (COP) capillary column is reported in a companion paper. 16 There are no extant suppressor designs that can be adapted to these columns with inner bores of 20−30 μm without introducing significant extra column broadening. A very low-volume, low-dispersion suppressor with sufficient suppression capacity is a critical requirement.…”
mentioning
confidence: 99%
“…9,10 However, to the best of our knowledge, only one practical study has been reported todate on the effects of column 3D geometry on retained solutes using liquid chromatography, which was a recent brief study investigating an open-tubular coiled anion exchange functionalized cycloolefin polymer capillary column. 11 Although relatively minor, the coiled column exhibited reduced b and c terms in relation to a straight capillary column of similar functionality and dimensions.…”
mentioning
confidence: 95%
“…Therefore, interest remains for experimental investigation of such effects, albeit with limitations on what can be practically achieved using traditional column formats. Experimental observations have been discussed previously in relation to both gas chromatography and supercritical fluid chromatography. , However, to the best of our knowledge, only one practical study has been reported to-date on the effects of column 3D geometry on retained solutes using liquid chromatography, which was a recent brief study investigating an open-tubular coiled anion exchange functionalized cycloolefin polymer capillary column . Although relatively minor, the coiled column exhibited reduced b and c terms in relation to a straight capillary column of similar functionality and dimensions.…”
mentioning
confidence: 98%